2010
DOI: 10.1163/156853810791069100
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour and territoriality of the strawberry poison frog (Oophaga pumilio) in dependence of the presence of ants

Abstract: The present study investigates foraging and territorial behaviour of the strawberry poison frog (Oophaga pumilio) in dependence of the presence of formicine and myrmicine ants, which constitute the main food source of the frogs. Species of the formicine ant genera Brachymyrmex and Paratrechina contain highly toxic alkaloids (pumiliotoxins), which the frogs incorporate and accumulate in their skin what may serve for predator deterrence. Twelve male frogs of two populations (primary and secondary forest) in Hito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In our study area, we mainly found myrmicine ants (Table 2). These ants are considered as potential dietary sources for histrionicotoxins which are the most frequent toxins in male frogs in Hitoy Cerere (Staudt et al, 2010). Our study showed ants to be more abundant in the territories of the females, indicating that ants influence the distribution and territorial behaviour of them.…”
Section: Aposematism and Diet Specializationmentioning
confidence: 59%
See 2 more Smart Citations
“…In our study area, we mainly found myrmicine ants (Table 2). These ants are considered as potential dietary sources for histrionicotoxins which are the most frequent toxins in male frogs in Hitoy Cerere (Staudt et al, 2010). Our study showed ants to be more abundant in the territories of the females, indicating that ants influence the distribution and territorial behaviour of them.…”
Section: Aposematism and Diet Specializationmentioning
confidence: 59%
“…The main purpose for aggressive territorial behaviour in male O. pumilio is to guarantee the availability of calling sites, access to females and suitable sites for courtship and oviposition (Meuche, Linsenmair, & Pröhl, 2012;Pröhl, 2003;Pröhl & Berke, 2001). Furthermore, males spend more time feeding in their territories, even though the availability of insect prey is the same in and outside of their territories (Staudt, Meneses Ospina, & Pröhl, 2010). Recent studies showed that also the females of O. pumilio exhibit intrasexual aggressive behaviour (Haase & Pröhl, 2002) particularly in the intensely used core areas of their home ranges (Meuche et al, 2011).…”
Section: Mannophryne Trinitatismentioning
confidence: 99%
See 1 more Smart Citation